Waste to Wound Care: Transforming Banana Peels into Burn Cream by the Minasari Farming Community in Jemur Wonosari, Surabaya - Kurniawan, Ilham; Sasongko, Purnomo Edi; Maghfiroh, Rahmatun Nisful; Nurhutami, Shofie Rindi; Yusuf, Aulia Islamiati; Hakim, Cindy Aisyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The utilization of banana peels as a natural remedy for minor burn wound healing and antimicrobial activity has garnered increasing attention amidst the growing interest in plant-based traditional medicine. This study investigated the bioactive components present in banana peels, including flavonoids, tannins, and polyphenols, which contribute to wound healing and the prevention of infections. Conducted as a community engagement initiative in Jemur Wonosari Sub-district, Surabaya, the activity was designed to be replicable at the household level using simple tools and locally available materials. The preparation process involved cleaning the peels, heating them with virgin coconut oil, and optionally adding natural honey to enhance antibacterial properties. Findings highlight the potential of banana peels as an effective natural burn ointment with antimicrobial and antioxidant properties, while also supporting circular economy principles through the utilization of agricultural waste. Further research is needed to standardize formulations and clinically validate the widespread use of ointments based on banana peels.